CHANGING ROLE OF SPECIAL LIBRARY PROFESSIONALS IN DIGITAL ENVIRONMENT - G.R., Rajashekara; Biradar, B.S. (International Journal of Research -GRANTHAALAYAH, 2022)
The role of library professional is vital in special libraries. Professional should be a knowledge manager, information scientist, a good administrator, and a technology person to cope up technical aspect of Special Library. In nutshell professionals in special libraries shall be required to have change in their attitude and behavior to make them fit to the profession. They must be conversant with changing technology and must have access to innovation taking place in specific areas and acquiring specialization in their professional skills. This creates a congenial atmosphere for dissemination of information and its use in different research activities. Consistent training programs will help staff to improve their skills for their routine operations and services. Therefore, this paper made an attempt to give brief overview, challenges, development of special libraries and the key roles and responsibilities of special library professionals in digital library environment.